Dinamika Hubungan Islam dan Batak di Lembah Silindung: Perspektif Historis, 1830-1998 - Anwar, Syaiful; Rahman, Adi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This article discusses the dynamics of the relationship between Islam and Batak in the Silindung Valley, 1830-1998. The relationship between Islam and Batak is a relationship between religion and ethnicity that compete for influence. The arrival of Islam was followed by Christianity relating to the Batak in the Silindung Valley, forming a relationship triangle with different developments. Christianity is practiced by the majority of Batak in the Silindung Valley, although Islam was the first to arrive there. This article uses the historical method. This article uses the historical method, collecting contemporary sources and verifying them and then pouring them into historiography. The results of the source review show that the relationship between Islam and Batak in Silindung began with violence. Christianity was eventually chosen to be the majority religion. In its development, this relationship between religion and ethnicity had dynamics between Islam, Christianity, and Batak and ended with very high religious tolerance. The Silindung Valley eventually became a spiritual city, where the HKBP center was located there, while the Muslim community lived peacefully amidst the majority of Batak who were Christian.